Introducing Enterprise Risk Management Into the University Classroom: A Case Study. Issue 1 (March 2017) - Bruhn, Aaron; Whiting, Bronwen; Browne, Bridget; Higgins, Timothy; Tan, Chong It
Abstract: This article reports on the challenges faced when enterprise risk management courses (commonly studied by practitioners after several years of actuarial practice) were introduced into a postgraduate coursework degree, and taught concurrently with Actuarial Control Cycle (Part II) units. A small sample of students were interviewed, and the information gleaned from these interviews combined with the reflections provided by teaching staff is used to argue that although not problem‐free, the overall gain to students makes the project worthwhile. Assessment structure and use of class time in particular are examined as key features of the class, and potential improvements are suggested.